2018
DOI: 10.3389/fmicb.2018.02354
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bioactive Peptides by Lactobacillus Species: From Gene to Application

Abstract: To compensate for their amino acid auxotrophy, lactobacilli have developed the ability to hydrolyze proteins present in their environment. This proteolytic activity not only generates the free amino acids needed by the bacteria, but also a large variety of peptides, some of which are endowed with biological activities. These so-called “bioactive peptides” (BAPs) are interesting from a nutrition and healthcare perspective. The use of lactic acid bacteria (LAB) such as lactobacilli is an effective strategy for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(133 citation statements)
references
References 117 publications
2
99
0
Order By: Relevance
“…At this point, EPS purification via ethanol precipitation would be possible [139]. Depending on their properties, some cyclic dipeptides could be purified following the same approach [128], as well as 2-pyrrolidone-5-carboxylic acid (used as a humectant for dry skin and hair products) [121]. Other polar molecules such as sugars, small organic acids, and vitamins follow the same purification path as LA, and chromatographic methods would be necessary to separate them [132,135,136].…”
Section: Other Compounds With Industrial Potential Produced By Labmentioning
confidence: 99%
“…At this point, EPS purification via ethanol precipitation would be possible [139]. Depending on their properties, some cyclic dipeptides could be purified following the same approach [128], as well as 2-pyrrolidone-5-carboxylic acid (used as a humectant for dry skin and hair products) [121]. Other polar molecules such as sugars, small organic acids, and vitamins follow the same purification path as LA, and chromatographic methods would be necessary to separate them [132,135,136].…”
Section: Other Compounds With Industrial Potential Produced By Labmentioning
confidence: 99%
“…It has demonstrated that the type of inoculated microorganisms and the maturation time affect the concentration and size of peptides [136]. In the fermentation process, Bacillus subtilis [137,138], lactic acid bacteria (LAB) [139][140][141] and fungi [142] can release many different kinds of peptides with antioxidant activity. The three small peptides extracted from solid-state fermented sesame meal have demonstrated to have high DPPH radical and • OH scavenging ability and can reduce the level of malondialdehyde (MDA) in the serum and liver of mice, and improve the liver SOD and GSH-Px activity [143].…”
Section: Microbial Fermentation and Other Food Processingmentioning
confidence: 99%
“…is antioxidant capacity is mainly due to peptides released upon proteolysis during the fermentation period and the wide range of metabolic compounds formed by lactic acid bacteria which may act as electron donors reacting with free radicals to form more stable products [31,32]. Additionally, reductones formed during fermentation could react with free radicals to stabilize and terminate radical chain reactions [33].…”
Section: Resultsmentioning
confidence: 99%